Susceptibility assessment of debris flow from Baoxing River basin in Lushan earthquake zone, China. Issue 5 (October 2021) - Liu, Li-Na; Gao, Wen-Sheng; Xu, Chong; Chen, Jian
Abstract: As one of the prevalent natural disasters, debris flow often occurs in mountainous areas and causes severe property losses. This study primarily focuses on describing the spatial distribution of debris flow in the Baoxing River basin in the Lushan earthquake zone, Sichuan Province, and then a susceptibility index map. Geographic information systems (GIS) and certainty factor (CF) method were used to establish the relationship between debris flow sub-basins and six predisposing parameters: elevation, slope angle, slope aspect, geologic periods, lithology, and NDVI (normalized difference vegetation index). The results show that elevations above 2400m, slopes from 20° to 45°, slope aspects of east, south-east, and south, geologic periods of Sinian, Ordovician, and Carboniferous, NDVIs of -1 to 0.2, lithology areas such as pyroclastic and carbonate of sedimentary rock, and metamorphic rock containing mafic and magnesian are the special conditions that cause debris flows. Furthermore, it has higher susceptibility potential for the combination of topography and geological parameters, including these predisposing parameters of elevation, slope angle, slope aspect, geologic periods, and lithology, than other combinations. The debris flow susceptibility assessment results show that the moderate and above susceptibility area accounts for around 94% of the total basin area or 51.5% of the study area; more than half of the study area is debris flow-prone, indicating that debris flows are quite active in the study area.